2018
DOI: 10.1007/s00784-018-2556-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of deep carious lesions and pulps exposed during carious tissue removal in adults: a questionnaire study among dentists in Finland

Abstract: The results of this study can be utilized in continuing education, to raise awareness of management strategies supported by present scientific evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
2
28
1
1
Order By: Relevance
“…In previous studies of a similar nature carried out over the period 2007–2019, NSR was chosen by 34–71% (Fig. ) of the respondents worldwide . One of the possible reasons for the majority (85%) of dentists in Australia choosing SR might be that Australia has been at the forefront of caries risk assessment protocols and that modern theoretical concepts of cariology are taught in Australian universities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of a similar nature carried out over the period 2007–2019, NSR was chosen by 34–71% (Fig. ) of the respondents worldwide . One of the possible reasons for the majority (85%) of dentists in Australia choosing SR might be that Australia has been at the forefront of caries risk assessment protocols and that modern theoretical concepts of cariology are taught in Australian universities .…”
Section: Discussionmentioning
confidence: 99%
“…2) of the respondents worldwide. 20 One of the possible reasons for the majority (85%) of dentists in Australia choosing SR might be that Australia has been at the forefront of caries risk assessment protocols 21,22 and that modern theoretical concepts of cariology are taught in Australian universities. 23 Although a recent survey 23 on cariology teaching in Australia identified certain areas for improvement, the current study suggests that the implementation of the current clinical recommendations 6 on deep caries management in Australia is impressive.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be expected that the new evidence showing high success rates of vital pulp therapy in adults make age no longer a key factor in the choice of treatment in DCLs. In fact, a recent study investigating the preferred management methods of Finish dentists for DCLs in adult patients (24), has found that less invasive treatments are being selected into clinical practice by the majority of dentists in Finland. Similar results have been reported in a survey carried out to a sample of Spanish dentists (25).…”
Section: Discussionmentioning
confidence: 99%
“…The vast bulk of the management of deep caries and the exposed pulp is carried out by general dental practitioners (GDPs) rather than by referral to specialist centres. However, at present there is a lack of consensus between practitioners regarding the most appropriate way in which to manage deep caries (Croft et al 2019), with differences relating to country of practice (Stangvaltaite et al 2017, practitioner age (Chisini et al 2015, Schwendicke & G€ ostemeyer 2016 and type of employment (Chin et al 2016). GDPs have to be aware of the most up-to-date information on management of deep caries and VPT to be able to treat and refer appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…However, at present there is a lack of consensus between practitioners regarding the most appropriate way in which to manage deep caries (Croft et al . 2019), with differences relating to country of practice (Stangvaltaite et al . 2017, Schwendicke et al .…”
Section: Introductionmentioning
confidence: 99%